2016
DOI: 10.5455/ijmsph.2016.17122015293
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex hormone-binding globulin (SHBG) protein polymorphism on the levels of SHBG, testosterone, and insulin in healthy Indonesian men

Abstract: Background: Sex hormone-binding globulin (SHBG) is a protein. The synthesis of SHBG protein is encoded by SHBG gene. Protein polymorphism of SHBG can occur because of a mutation of D327N exon 8 in SHBG gene. D327N mutation causes the addition of glycosylation so that molecular weight of SHBG protein increases. Protein polymorphism of SHBG is suspected to affect the levels of SHBG, testosterone, and insulin in the blood circulation. Objective:To determine the effect of protein polymorphism of SHBG on the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
(64 reference statements)
2
11
0
1
Order By: Relevance
“…The other result of my study showed that SHBG levels in normal SHBG phenotype 31.70±13.78 nmol/L, while in variant SHBG phenotype 37.69±16.17 nmol/L. 21 Research conducted by Lapauw et al, also obtained comparable results with this study. 31 The results of another study in Brazil showed that SHBG levels correlated positively with age.…”
Section: Parwanto Mle Int J Res Med Sci 2017 Aug;5(8):3431-3437supporting
confidence: 80%
See 4 more Smart Citations
“…The other result of my study showed that SHBG levels in normal SHBG phenotype 31.70±13.78 nmol/L, while in variant SHBG phenotype 37.69±16.17 nmol/L. 21 Research conducted by Lapauw et al, also obtained comparable results with this study. 31 The results of another study in Brazil showed that SHBG levels correlated positively with age.…”
Section: Parwanto Mle Int J Res Med Sci 2017 Aug;5(8):3431-3437supporting
confidence: 80%
“…28 The other result of my study in normal SHBG phenotype showed that FT levels 0.065±0.01 nmol/L, while in variant SHBG phenotype 0.064±0.77 nmol/L. 21 The results of this study…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations